Assessment of Smile Line and Attractiveness in a Group of Thai University Students - Benjasupattananan, Supranee; Sirikururat, Papatpong (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2023)
Objectives: To determine the prevalence of smile line in a group of Thai university students and to evaluate the attractiveness of smile line combined with tooth shape. Materials and Methods: Four hundred university students (159 males and 241 females, ages 20-30 years old) voluntarily participated in the study. Maximum smile photographs were taken from each participant. Smile line was classified as low, average, high and very high smile line. Gingival display of the high smile line group was measured by using a 2-mm diameter reference dot which was placed on the middle of the labial surface of the right maxillary central incisor. All participants were enquired to rate the attractiveness score of twelve photographs which represented smile lines combined with tooth shapes. Results: Most of participants exhibited average smile line (57.50%), followed by high (34.25%) and low smile line (8.25%), respectively. The highest proportions were average smile line for both male and female, 63.52% and 53.53%, respectively. The proportions of smile line types between male and female were statistically significant difference (p < 0.05). Among 12 smile types, rating score of average smile line with square tooth shape received statistically significant highest score from other smile types (p < 0.05). Whereas, all three bottom scores were square, ovoid and triangle tooth shape in low smile line. Conclusions: The average smile line was the most frequently observed in both genders. The average smile line in combined with square tooth shape was scored as the most attractive. > ว.ทันต.มศว ปีที่ 16 ฉบับที่ 1 พ.ศ. 2566 หน้า 11-22. > SWU Dent J. 2023;16(1): 11-22.